Driving lessons - supporting academic development in a private higher education space. - Ballam, John (The IIE., 2012)
At Varsity College (VC) and throughout the divisions of The Independent Institute of Education, academic developers are known by the title of ‘Academic Development Coordinators’. This paper reflects critically on the development of this role. Some of the critical insights gained in this role are examined, from the author’s initial appointment as an academic development coordinator based at one of the regional campuses, and then subsequently as the national academic development coordinator in which academic leadership is provided for the regional campus academic development coordinators. Thereafter three pertinent issues are explored with which the newly evolved role still grapples. Firstly, the unconscious ignorance of the complexity embedded within this role. Secondly, there is the profound shift in awareness that occurs in academic identity, from that of subject expert to a teaching and learning professional managing an academic culture. Finally, there exists the issue of how to manage sensitively an academic developer within the context of the institution’s performative education agenda.
Keywords: Private higher education - South Africa; Academic identity; Teaching and learning; Academic culture; Performative education